Antiferromagnetic Topological Insulator with Nonsymmorphic Protection in Two Dimensions - Niu, Chengwang; Wang, Hao; Mao, Ning; Huang, Baibiao; Mokrousov, Yuriy; Dai, Ying (Physical Review Letters, 2020)
The recent demonstration of topological states in antiferromagnets (AFMs) provides an exciting platform for exploring prominent physical phenomena and applications of antiferromagnetic spintronics. A famous example is the AFM topological insulator (TI) state, which, however, was still not observed in two dimensions. Using a tight-binding model and first-principles calculations, we show that, in contrast to previously observed AFM topological insulators in three dimensions, an AFM TI can emerge in two dimensions as a result of a nonsymmorphic symmetry that combines the twofold rotation symmetry and half-lattice translation. Based on the spin Chern number, Wannier charge centers, and gapless edge states analysis, we identify intrinsic AFM XMnY (X=Sr and Ba, Y=Sn and Pb) quintuple layers as experimentally feasible examples of predicted topological states with a stable crystal structure and giant magnitude of the nontrivial band gaps, reaching as much as 186 meV for SrMnPb, thereby promoting these systems as promising candidates for innovative spintronics applications.
CRIS-Team Scopus Importer:2023-03-27